Comparative genomics approaches to understanding virulence and antimicrobial resistance of Salmonella typhimurium ST1539 isolated from a poultry slaughterhouse in Korea - Kim, Eunsuk; Park, Soyeon; Cho, Seongbeom; Hahn, Tae Wook; Yoon, Hyunjin (Journal of Microbiology and Biotechnology, 2019)
Non-typhoidal Salmonella (NTS) is one of the most frequent causes of bacterial foodborne illnesses. Considering that the main reservoir of NTS is the intestinal tract of livestock, foods of animal origin are regarded as the main vehicles of Salmonella infection. In particular, poultry colonized with Salmonella Typhimurium (S. Typhimurium), a dominant serotype responsible for human infections, do not exhibit overt signs and symptoms, thereby posing a potential health risk to humans. In this study, comparative genomics approaches were applied to two S. Typhimurium strains, ST1539 and ST1120, isolated from a duck slaughterhouse and a pig farm, respectively, to characterize their virulence and antimicrobial resistance-associated genomic determinants. ST1539 containing a chromosome (4,905,039 bp; 4,403 CDSs) and a plasmid (93,876 bp; 96 CDSs) was phylogenetically distinct from other S. Typhimurium strains such as ST1120 and LT2. Compared to the ST1120 genome (previously deposited in GenBank; CP021909.1 and CP021910.1), ST1539 possesses more virulence determinants, including ST64B prophage, plasmid spv operon encoding virulence factors, genes encoding SseJ effector, Rck invasin, and biofilm-forming factors (bcf operon and pefAB). In accordance with the in silico prediction, ST1539 exhibited higher cytotoxicity against epithelial cells, better survival inside macrophage cells, and faster mice-killing activity than ST1120. However, ST1539 showed less resistance against antibiotics than ST1120, which may be attributed to the multiple resistanceassociated genes in the ST1120 chromosome. The accumulation of comparative genomics data on S. Typhimurium isolates from livestock would enrich our understanding of strategies Salmonella employs to adapt to diverse host animals.
Keywords: Abattoirs; Animals; Anti-Bacterial Agents; Bacterial Proteins; Cell Survival; Drug Resistance, Bacterial; Female; Genome, Bacterial; HeLa Cells; Humans; Mice; Mice, Inbred BALB C; Phylogeny; Plasmids; Poultry; Prophages; Republic of Korea; Salmonella Infections, Animal; Salmonella typhimurium; Serogroup; Swine; Virulence; Antibiotic resistance; Comparative genomics; Salmonella typhimurium; Virulence